First order differential equations induced by the infinite servers queue with poisson arrivals transient behavior probability distribution parameters study as time functions - Ferreira, M. A. M. (16th Conference on Applied Mathematics, APLIMAT 2017, 2017)
The M|G|? queue system state transient probabilities, considering the time origin at the beginning of a busy period, mean and variance monotony as time functions is studied. These studies, for which results it is determinant the hazard rate function service time length, induce the consideration of two differential equations, one related with the mean monotony study and another with the variance monotony study, which solutions lead to some particular service time distributions, for which those parameters present specific behaviors as time functions.